Effects of the Covid-19 and natural agricultural shocks on preferences of farmers - Hamza Umer; Takashi Kurosaki (Humanities & Social Sciences Communications)
Abstract It is imperative to examine how different negative shocks influence preferences because preferences influence micro level decisions that provide foundations for macro-level outcomes. We contribute to this domain by reporting an incentivized field experiment that examined the effects of agricultural income shocks driven by either the Covid-19 or other natural calamities on preferences (risk-taking, impatience, generosity and fairness) of Pakistani farmers. We find that the Covid-19 shock reduced impatience and generosity while the natural shock increased risk-aversion. Our findings suggest that despite having a similar impact on farmers’ agricultural income, the two shocks influence a different set of preferences, and hence, we need to measure them both to identify their precise impact on preferences. Overall, these results offer new information about the relative impacts of the Covid-19 and natural shocks on preferences and help us understand the wealth and age-based heterogeneous effects of these shocks.